Radical product thinking : the new mindset for innovating smarter - Dutt, R. (Radhika) (Berrett-Koehler Publishers, Inc., 2021)
"Iteration rules product development, but it isn't enough to produce dramatic results. This book champions Radical Product Thinking, a systematic methodology for building visionary, game-changing products"--